2009
DOI: 10.1007/s11060-009-9919-z
|View full text |Cite
|
Sign up to set email alerts
|

Molecular properties of CD133+ glioblastoma stem cells derived from treatment-refractory recurrent brain tumors

Abstract: Glioblastoma multiforme (GBM) remains refractory to conventional therapy. CD133+ GBM cells have been recently isolated and characterized as chemo-/radio-resistant tumor-initiating cells and are hypothesized to be responsible for post-treatment recurrence. In order to explore the molecular properties of tumorigenic CD133+ GBM cells that resist treatment, we isolated CD133+ GBM cells from tumors that are recurrent and have previously received chemo-/radio-therapy. We found that the purified CD133+ GBM cells sort… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
126
1
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 113 publications
(134 citation statements)
references
References 72 publications
5
126
1
2
Order By: Relevance
“…41 Recent study showed that FABP7 preferentially expresses in CD133-positive glioblastoma cells. 42,43 Here, we also found that FABP7 is highly expressed in U251 sphere cells and respond to hypoxia-induced activation of Notch signaling. What remains to be explored is whether FABP7 serves as a marker for GSC and its role in the hypoxiamediated maintenance.…”
Section: Discussionsupporting
confidence: 58%
“…41 Recent study showed that FABP7 preferentially expresses in CD133-positive glioblastoma cells. 42,43 Here, we also found that FABP7 is highly expressed in U251 sphere cells and respond to hypoxia-induced activation of Notch signaling. What remains to be explored is whether FABP7 serves as a marker for GSC and its role in the hypoxiamediated maintenance.…”
Section: Discussionsupporting
confidence: 58%
“…This led to the identification of 12 phosphatases potentially involved in the stem-like phenotype of GSCs (Figures 1c and d). Six of the twelve candidate genes (PPEF1, ENPP1, PTPN9, PPP4C, PPP2R2A and DUSP5) were found to be highly expressed in astrocytic gliomas compared with adult normal brain and/or to be essential for stem cell maintenance (Supplementary Figure S2A) [17][18][19][20][21][22] and hence selected for validation studies. Decreased CD133 level 6 days posttransduction was confirmed in NCH421k (GSCs used in the primary screen) and in additional GSCs (NCH441, NCH644) in two independent experiments using the two shRNAs that showed the strongest CD133 reduction in the primary screen (Figure 1e; Supplementary Figure S2B).…”
Section: Resultsmentioning
confidence: 99%
“…In our study, the TK gene was delivered into cells with a lentiviral vector that has the ability to infect non-dividing cells, rendering it more suitable than the oncoretroviral vector to target slow-growing CD133 þ glioblastoma stem cells. 33 Except for the Cx43-negative GBM9 cells, all the other cell lines displayed a BE with values within the 10-30% range ( Figure 5). The BE intensities did not correlate with the localization of Cx43, and did not reflect the gap-junctional intercellular communication measured by calcein transfer.…”
Section: Discussionmentioning
confidence: 95%